Analysis Level of Animal Welfare Knowledge in Medan City Slaughterhouse - E. Mirwandhono; A. Sadeli; Hasnudi; N. Ginting; Ramadhan, Muhammad (Jurnal Peternakan Integratif, 2021)
Slaughterhouses has a very important role in the chain system for the availability of meat procurement. This research aims to analyze the level of knowledge of animal welfare and implementing it in Medan City Slaughter House. This research was conducted at the Medan City Slaughterhouse located on Jalan Rumah Potong Hewan, Mabar Hilir Village, Medan Deli Subdistrict, Medan City, North Sumatra in August 2021. The method used in this research is a qualitative descriptive research method.The results showed that the level of knowledge was already in the category of very good. The group of slaughterer respondents had the highest percentage of answer scores at 100% followed by animal controllers at 95.36% and cattle traders at 88.62%. The application of animal welfare aspects in the process of slaughtering cattle in Medan City Slaughterhouse is already in the category of very good with the percentage of conformity rate based on the regulations and provisions of Meat and Livestock Australia ranging from 80% to 100%.